THE USE OF VIDEO PRESENTATION TO CREATE A GOOD ATMOSPHERE AND DEVELOP STUDENTS’ SENSORY PREFERENCES WITHIN EXTENSIVE READING CLASS - Fariska Pujiyanti; Frida Unsiah (Universitas PGRI Semarang, 2014)
In Extensive Reading class, students are often asked to present what they have read. However, when it comes for them to present the material, oral presentation seems to be a common choice. When some students present their material, the rests wait for their turn. The uneasy atmosphere is created when they are waiting. Challenge is taken as how to create a good atmosphere in class. This challenge triggered the writers to conduct a small research on creating a lively Extensive Reading class by video presentation. The respondents of our research were 35 students who took the subject. Sensory preferences of four dimensions of learning style that are likely associated with L2 learning by Ehrman and Oxford (1990) become the basismethod of this research. In this method, students are asked to read and make summary on the reading materials in the form of video. Based on the questionnairres given, the students admitted that they were more interested to have video presentation than just a common oral presentation because the class is more lively and the students’ sensory preferences are developed.